Implementation of Ethnoscience-Based Electronic Student Worksheets on Ecosystem Material in Elementary Schools to Improve Students' Curiosity Character - Anggraini, Nadya; Asante, Joyce Nsiah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This study explores the implementation of ethnoscience-based electronic student worksheets to enhance elementary students' understanding of ecosystem concepts and curiosity. By integrating local cultural wisdom with digital learning tools, the study offers a contextual and engaging approach to science education. Using an experimental pretest-posttest control group design, 60 fifth-grade students were divided into experimental and control groups. The experimental group utilized ethnoscience-based electronic worksheets, while the control group followed conventional learning methods. Data collection involved ecosystem concept tests and curiosity questionnaires, analyzed using descriptive statistics and t-tests. Results revealed that the experimental group demonstrated significant improvements in understanding ecosystem concepts (mean increase of 22.9 points) and curiosity (mean increase of 1.2 points), compared to the control group, which recorded increases of 11.9 points and 0.6 points. These findings underscore the effectiveness of integrating local wisdom into teaching materials to bridge the gap between theoretical knowledge and real-life applications. The worksheets encourage students to observe, question, and explore, fostering both cognitive and affective learning outcomes. This approach not only strengthens conceptual understanding but also promotes cultural appreciation and pride among students. The study's novelty lies in its combination of ethnoscience with digital technology, offering an innovative and interactive educational resource that aligns with modern educational demands while preserving cultural heritage. It concludes that ethnoscience-based electronic worksheets are a valuable tool for holistic learning.